"Living systems infrastructure" of Kolkata: exploring co-production of urban nature using historical urban political ecology (HUPE). (April 2022) - Mukherjee, Jenia
Capital investment-laden green blue infrastructures (GBI) are being globally celebrated as harbingers of urban resilience to address environmental risks. These technocratic designs exclude historical and micro-political processes shaping urban environments. It is within this context that exposure to social sciences frameworks remains significant. Here, I formulate and deploy historical urban political ecology (HUPE) to explore the mutual relationship between Kolkata and her wetlands, finally demonstrating that cities need to be perceived as complex and adaptive "living systems infrastructure" evolved over time, across an intersecting array of technological apparatuses and social arrangements through constant interactions between human and non-human actors. Beyond linear choreographies of power equations, HUPE conveys the "plural" by exemplifying collaborations, compulsions and contingencies that mediate urban ecologies. I argue that HUPE is an enabling framework, eliciting emancipatory possibilities within political ecology by envisioning the translation of epistemological insights into implementable actions, towards more just and resilient urban ecologies of future.